Conceptualization of Islamic Spiritual Intelligence (ISI) in the Islamic Financing Adoption - Siti Nor Amira Mohamad; Fadziani Yaakub; Mohamad Yazis Ali Basah (Macrothink Institute, 2024)
Business and Management Horizons Volume 11 No 2 Page (1-9)